Determinant Of Firm Value: Debt Maturity As Moderator (Study In Manufacturing Industry In Indonesia) - Ida Ayu Surasmi, Ni Luh Putu Wiagustini, Ida Bagus Anom Purbawangsa; Ida Bagus Panji Sedana (International Journal of Advanced Science and Technology, 2020)
This research aims to examine and explain the effect of asset growth, leverage, dividend policy, taxes and inflation on firm value, with debt maturity as a moderator. This research takes a sample of manufacturing companies listed on the Stock Exchange Indonesian Stock Exchange (IDX) in 2012 to 2017. Test results show that asset growth, leverage, and tax have a positive effect on firm value, while dividend policy has no effect on firm value. Debt maturity strengthens the effect of asset growth, leverage, and dividend policy on firm value.